2020
DOI: 10.3892/etm.2020.8696
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of puerarin against burn‑induced heart injury in rats

Abstract: The present study evaluated the potential protective effects of puerarin and its associated mechanism on burn-induced myocardial damage. A total of 40 healthy adult Wistar rats were randomly divided into four groups: i) Sham; ii) burn; iii) burn + puerarin; and iv) puerarin. Serum levels of interleukin (IL)-1β, tumor necrosis factor-α (TNF-α) and IL-6 were measured using ELISA. Myeloperoxidase (MPO) activity and malondialdehyde (MDA) levels were determined in myocardial homogenates using a commercial assay kit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Numerous studies have indicated that many traditional Chinese herbs have potent anti-inflammatory and antioxidant properties [ 12 15 ]. Due to various diseases, Puerarin can effectively reduce oxidative stress and inflammation in the myocardium [ 37 , 38 ]. In addition, through our research, we demonstrate that Puerarin significantly reduced oxidative stress indicators (MDA, GSH, and SOD) and inflammatory cytokines (TNF-α, IL-6, and IL-10) in the serum of LPS model rats.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have indicated that many traditional Chinese herbs have potent anti-inflammatory and antioxidant properties [ 12 15 ]. Due to various diseases, Puerarin can effectively reduce oxidative stress and inflammation in the myocardium [ 37 , 38 ]. In addition, through our research, we demonstrate that Puerarin significantly reduced oxidative stress indicators (MDA, GSH, and SOD) and inflammatory cytokines (TNF-α, IL-6, and IL-10) in the serum of LPS model rats.…”
Section: Discussionmentioning
confidence: 99%
“…A growing number of studies have indicated that both exogenous and endogenous ROS participate in the pathogenesis of pulmonary disorders, such as ARDS, COPD, ↑Nrf2 translocation, ↑HO-1, ↓pulmonary vascular remodeling via inhibiting EndMT [87,237,238] ↓pulmonary fibrosis, ↓cyclin D1, ↓cyclin E1, ↓cyclin B1, ↓Bcl-2 protein, ↑p53, ↑p21, ↑cleaved caspase-3 protein [234] repress the adhesion of bacteria [235] ↑SOD, ↑catalase, ↑glutathione peroxidase ↓ type I collagen I, ↓endogenous TGF-β1, ↓α-SMA [236,238] ↓MAPK and NF-κB signaling pathways [40,237] ↓TNF-α, ↓IL-6, ↓IL-1β, ↓MCP-1 [237] Asiatic acid ↓pulmonary fibrosis [241,242] ↓TGF-β1, ↓Collagen I, ↓Collagen III, ↓α-SMA, ↓TIMP-1, ↓NLRP3 inflammasome, ↓Smads and ERK1/2 [242][243][244] ↓ROS, ↓neutrophil elastase (NE) activity, ↓MCP-1, ↓recruitment of inflammatory cells, ↓MAPKs, ↓NF-kB, ↑Nrf2, ↑HO-1, ↑SOD3, ↑catalase [41,243,244] Celastrol ↓NF-κB signaling pathway, ↓NLRP3 activity [245][246] ↓IL-8, ↓TNFα, ↓MCP -1, ↑SOD, ↑catalase, ↓Ednrb/Kng1 signaling pathway [248] ↓MMP 2/9, ↑Nrf2, ↑HO-1, ↑GSTs, ↑NQO1 [88] ↓Bax, ↓caspase-3 [249] Fisetin ↓TNFα, ↓PARP-1 [253] ↓neutrophils and macrophage infiltration, ↓MPO activity, ↓TLR4 expression, ↓NF-κB [254,255] ↑Nrf2, ↑HO-1, ↑glutathione peroxidase-2, ↑reduced glutathione, ↑SOD [89] Galangin ↓TGF-β1-ROS-MAPK pathway, ↓goblet cell hyperplasia, ↓collagen deposition, ↓α-SMA expression, ↓VEGF, ↓MMP-9 [257] ↓IL-4, 5, 13, 17, ↓TNF-α, ↓NO, ↓ROS, ↓EPO, ↓IgE, ↑IFN-γ, ↑PPARγ activity [258] Kaempferol ↓TAK1, ↓NF-κB, ↓MAPK, ↓cytokine production [45,262,264,265] ↓ROS …”
Section: Discussionmentioning
confidence: 99%
“… 88 Celastrol also reduced the protein levels of Bax and caspase-3 activity to induce anti-inflammatory and anti-apoptotic effects in burn-induced lung injury. 249 …”
Section: Chinese Herbal Medicinesmentioning
confidence: 99%
“…Our findings demonstrated that celastrol was able to reduce both SARS-CoV-2 viral load and IL-6 production in two human cell lines, suggesting that this compound exerts anti-SARS-CoV-2 effects of clinical relevance to face the current pandemic. Several pharmacological applications of celastrol are associated with Covid-19 severity, including comorbidities such as obesity, diabetes, hypertension, and metabolic syndrome [95][96][97][98] , and pathological events such as non-homeostatic production of pro-inflammatory cytokines, thrombus generation, and formation of neutrophil extracellular traps [99][100][101] . Celastrol is currently under clinical trials to treat a variety of diseases, including different types of cancer, neurodegenerative disorders, and inflammatory conditions such as rheumatoid arthritis, psoriasis, and Crohn's disease [102][103][104][105][106] .…”
Section: Discussionmentioning
confidence: 99%